PENGGUNAAN ]NFORMASI AKUNTANSI UNTUK MEMPREDIKSI RETURN SAHAM PADA PERUSAHAAN REAL ESTAT DAN PROPERTT YANG TERDAFTAR DI BURSA EFEK JAKARTA - Felicia P. Bahari; Wirawan E.D. Radianto (Fakultas Bisnis UKDW, 2007)
The role of Jinancial ratio analysis is to investigate whether finorcial information is useful to predict stock return and corporate financial condition in the future.This study examines the use of financial ratio to predict stock return for one and two years ahead. This study is bosed on research by fuasikal (2002) and use listed real estate industies in 1999 as sample. CAR is used as proxy of stock return and window periode is used seven day before ond after financial reporting publication for 2000 and 2001. Financial reporting is taken from ICMD for 2001. Using multiple regressin, the outcome fum this research, price tobook value influence positively to predict stock return for two years ahead. While account receivable turnover ratio significantly can predict stock return foir one year ahead.Keywords: Financial information, stock return, financiol ratio, realestate and property.